2016
DOI: 10.1186/s13046-016-0340-0
|View full text |Cite
|
Sign up to set email alerts
|

Clinical significance of pancreatic circulating tumor cells using combined negative enrichment and immunostaining-fluorescence in situ hybridization

Abstract: BackgroundCirculating tumor cells (CTCs) hold great potential in both clinical application and basic research for the managements of cancer. However, it remains to be an enormous challenge to obtain efficient detection of pancreatic CTCs. New detection platforms for the detection of pancreatic CTCs are urgently required.MethodsIn the present study, we applied a newly-developed platform integrated subtraction enrichment and immunostaining-fluorescence in situ hybridization (SE-iFISH) to analyze clinical signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
77
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 80 publications
(82 citation statements)
references
References 42 publications
(54 reference statements)
4
77
1
Order By: Relevance
“…Several modified device have been developed for better detection of pancreatic CTCs. Immuno-FISH platform is a negative-enrichment method for CTC detection and our preliminary results showed that the sensitivity could reach 100% by combining CTC and CA19-9 36. The PCR-based strategy have also been reported to detect pancreatic CTCs, but the platform may produce false-positive results 37, 38.…”
Section: Ctc Detection Platforms For Pancreatic Cancermentioning
confidence: 85%
“…Several modified device have been developed for better detection of pancreatic CTCs. Immuno-FISH platform is a negative-enrichment method for CTC detection and our preliminary results showed that the sensitivity could reach 100% by combining CTC and CA19-9 36. The PCR-based strategy have also been reported to detect pancreatic CTCs, but the platform may produce false-positive results 37, 38.…”
Section: Ctc Detection Platforms For Pancreatic Cancermentioning
confidence: 85%
“…These studies demonstrated SE-iFISH CTC detection 91% positive rate for breast cancer patients (7), a sensitivity of 88% and specificity of 90% in pancreatic cancer and healthy individuals at the cutoff value of 2 cells/7.5 ml (8), and a sensitivity of 90.9% and specificity of 82.4% in colorectal cancer and healthy individuals at the cutoff value of one cell/7.5 ml (9). From these studies, CTC detection by SE-iFISH showed high sensitivity and specificity for distinguishing breast cancer, pancreatic cancer and colorectal cancer from healthy people.…”
Section: Introductionmentioning
confidence: 90%
“…At the same time, Cell Search system has an inherent limitation that hampers the detection of EpCAM-negative CTCs. This drawback is overcome by a negative enrichment method (CD45−) combined with immunostaining-fluorescence ISH, which is able to yield CTCs independently of EpCAM expression and cell size (Gao et al 2016). A possible limitation, in case of earlystage cancer, is the difficulty to count CTCs as they are expected to be few, corresponding to a low sensitivity of the method.…”
Section: Part 1 Circulating Tumor Cellsmentioning
confidence: 99%